Data protection and taxpayers' rights : challenges created by automatic exchange of information - Wöhrer, Viktoria (WU Institute for Austrian and International Tax Law European and international tax law and policy series., 2018)
This book examines the scope of exchange of information and the design of exchange of information provisions in relation to EU data protection requirements and guarantees.